2002
DOI: 10.1034/j.1398-9995.2002.1o3532.x
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of subcutaneous birch pollen immunotherapy - a one-year, randomised, double-blind, placebo-controlled study

Abstract: High-dose, subcutaneous IT is efficacious and safe in patients with severe birch pollen rhinoconjunctivitis and asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 32 publications
8
74
0
2
Order By: Relevance
“…Clinical efficacy (reduction of symptoms and/or need for medications) has been confirmed with grass (1102,1104,(1650)(1651)(1652)(1653)(1654)(1655), birch (1650,1651,(1656)(1657)(1658)(1659), ragweed (1660), Russian thistle (1661), Parietaria pollen (1662,1663), mites (1664)(1665)(1666)(1667)(1668)(1669) and cat (1670). It should be noted that three of the studies (1104,1660,1670) clearly demonstrated that the clinical effect is dose dependent.…”
Section: Aria: 2008 Updatementioning
confidence: 97%
“…Clinical efficacy (reduction of symptoms and/or need for medications) has been confirmed with grass (1102,1104,(1650)(1651)(1652)(1653)(1654)(1655), birch (1650,1651,(1656)(1657)(1658)(1659), ragweed (1660), Russian thistle (1661), Parietaria pollen (1662,1663), mites (1664)(1665)(1666)(1667)(1668)(1669) and cat (1670). It should be noted that three of the studies (1104,1660,1670) clearly demonstrated that the clinical effect is dose dependent.…”
Section: Aria: 2008 Updatementioning
confidence: 97%
“…For olive pollen, preseason SCIT has shown to produce significant improvement both in nasal and bronchial symptoms, and a decrease in the consumption of rescue medication [95]. For birch pollen, SCIT induced immunological changes in T cell populations and Ig subtypes [96,97] and a reduction of symptom score for rhinoconjunctivitis and asthma and total medication score [98]. Several randomized trials have evaluated the efficacy of SCIT for grass pollen allergy in patients with chest symptoms.…”
Section: Subcutaneous Immunotherapymentioning
confidence: 99%
“…21 Bødtger ve ark. 22 35 has ta da, Wal ker ve ark. 23 40 has ta da çift-kör pla se bo kon trol lü ola rak uy gula dık la rı sub ku tan ASİ so nun da semp tom lar da, ilaç ge rek si ni min de ve cilt tes ti nin re ak ti vi te sin de azalma sap ta mış lar dır.…”
Section: Tar Tiş Maunclassified